2010
DOI: 10.1007/s00040-010-0069-2
|View full text |Cite
|
Sign up to set email alerts
|

Leaf cutter ants (Atta cephalotes) harvest baits offering sodium chloride rewards

Abstract: Recent studies of attraction to sodium chloride baits suggest that diverse ant species forage for salt. We used experimental presentations of salt baits to test whether leaf cutter ants (Atta cephalotes) are attracted to and harvest salt-treated paper baits that offer no other resources. Atta foragers were most attracted to sucrose baits (positive control), but more foragers touched and cut salt-treated baits than water-treated baits (negative control). Furthermore, the ants removed more paper from the salt ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 11 publications
2
10
0
1
Order By: Relevance
“…1). We extend previous findings on Atta salt attraction (O'Donnell et al, 2010) and demonstrate that Atta forage specifically for sodium. Treatments Leafcutter ant sodium foraging 437 differed highly significantly in the weight of paper removed (F 3,12 = 10.05, P = 0.0014) and area removed (F 3,12 = 5.68, P = 0.012).…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations
“…1). We extend previous findings on Atta salt attraction (O'Donnell et al, 2010) and demonstrate that Atta forage specifically for sodium. Treatments Leafcutter ant sodium foraging 437 differed highly significantly in the weight of paper removed (F 3,12 = 10.05, P = 0.0014) and area removed (F 3,12 = 5.68, P = 0.012).…”
Section: Resultssupporting
confidence: 89%
“…Atta foraging was strongest after dark, so baits were placed at approximately 22.00 hours local time and left overnight (O'Donnell et al, 2010). The first bait was placed 3 m from a nest entrance; baits were separated by a 3 m distance.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…To our knowledge, only two other studies have investigated the sodium requirements of ants. O'Donnell et al (2010) found that leafcutter ants (Atta cephalotes) in Costa Rica cut and removed more salt-soaked than water-soaked paper baits, although they most strongly preferred the sugarsoaked option, and Kaspari et al (2010) found that ant recruitment to NaCl baits increased with distance from a salted road at Harvard Forest. Thus, while it is becoming increasingly clear that ants will recruit to sodium in many ecosystems, the consequences of sodium intake for ant nutrition and fitness have received little attention.…”
Section: Introductionmentioning
confidence: 99%